POLA AGROFORESTRI MASYARAKAT DI DESA MOPOLO KECAMATAN RANOYAPO KABUPATEN MINAHASA SELATAN - Eka Maryuni Toding; Semuel P. Ratag; Euis F.S. Pangemanan (COCOS, 2022)
Abstract Agroforestry is a land management system consisting of a combination of trees, shrubs, or seasonal crops often accompanied by livestock in the same land. The objectives of agroforestry land management are to maximize land productivity, create jobs, and increase income in rural areas. Mopolo Village is located in Ranoyapo District, South Minahasa Regency, North Sulawesi Province. This study aims to identify the agroforestry pattern applied by the community in Mopolo Village, South Minahasa Regency and describe the advantages and disadvantages of the agroforestry pattern applied by the community in Mopolo Village, South Minahasa Regency. This study uses a survey method by conducting interviews as a data collection tool. Based on the results of the study, it showed that the agroforestry patterns applied by farmers in Mopolo Village were agrisilvicultural patterns, agrosilvopasture patterns, and agrosilvofishery patterns. The advantages of applying the agroforestry pattern are increasing farmers' income and livestock owned by farmers getting feed from managed land while the lack of applying the agroforestry pattern is that the plants used by farmers in Mopolo Village are attacked by pests, which until now have not known the type of pests that attack and other things. What disturbs plant growth is the presence of released chickens that enter the land and disrupt plant growth. Keywords : agroforestry pattern, agroforestry, Mopolo Village, Ranoyapo District.